The Mediating Effect of Classroom Learning Environment on the Relationship Between Filipino Language Anxiety and Coping Strategies - BERNAL, ARNEL II (International Journal of Language and Literary Studies, 2021)
This study aims to identify the effect of the classroom-learning environment as a mediator on the relationship between Filipino language anxiety and the coping strategies of college students. This research was undergone by quantitative research design using descriptive and correlation method via mediation analysis. This study uses stratified random sampling; the data was gathered using survey questionnaires involving 300 respondents from first-year colleges to fourth-year college) students. In response to the hypothesis of this study, correlation analysis was used together with the Pearson r and Mediation Analysis using Sobel z Test. The result has shown that Filipino language anxiety and coping strategies have a strong and positive relationship. A strong and positive relationship was also found between Filipino language anxiety and classroom learning environment and the relationship between classroom learning environment and coping strategies. Furthermore, using the Sobel z test, the research found that the effect of the classroom-learning environment partially mediated the relationship between Filipino language anxiety and coping strategies.